Electoral justice in Brazil: autonomy and institutional resources - Maués, Antonio Gomes Moreira (2025)
The article analyzes the institutional resources that allowed the Electoral Court in Brazil to preserve its autonomy in the face of pressure exerted by the Bolsonaro government. After a summary of the history of the Electoral Court before the 1988 Constitution, the work highlights the characteristics of the institutional design of the Electoral Court in the current democratic regime, analyzing the different aspects of its autonomy based on constitutional and legal norms and empirical data on its functioning. The article then demonstrates that the Electoral Court's different electoral governance functions exercises, including the elaboration of electoral rules, generated a process of self-reinforcement of its autonomy, increasing the costs of eventual attempts to reverse it. This process was also guaranteed by the institutional articulation of the Superior Electoral Court with the Federal Supreme Court, in which the latter court acts as a self-referential veto point, which preserves the decisions of the Electoral Court